2010
DOI: 10.1590/s1516-89132010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thermostable α- amylase production by Streptomyces erumpens MTCC 7317 in solid-state fermentation using cassava fibrous residue

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Bacillus amyloliquefaciens, Streptomyces erumpens MTCC 731, Bacillus amyloliquefaciens KCP2, and Aspergillus oryzae S2 synthesize alpha-amylase by CCD method. 51,[59][60][61]…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Bacillus amyloliquefaciens, Streptomyces erumpens MTCC 731, Bacillus amyloliquefaciens KCP2, and Aspergillus oryzae S2 synthesize alpha-amylase by CCD method. 51,[59][60][61]…”
Section: Response Surface Methodologymentioning
confidence: 99%
“…Processing of cassava for products like starch and sago produces solid waste namely, fibrous cassava pulp (cassava bagasse) which consists of 15-70% starch per solid dry weight entrapped in fibrous matrix of cellulose and non-starch polysaccharides [4,5]. The utilization of cassava pulp which is rich in organic carbohydrates for the production of chemicals such as organic acids, enzymes, single cell protein, amino acids, pigments, etc., and renewable energy like ethanol, butanol [6] is of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Mitchell et al (2000) and Neifar et al (2011), whereby they reported that in SSF system the microorganism obtained water from the moisture held within the substrate particles which is essential for fungal growth, metabolism and the production of secondary metabolites. Moisture holding capacity has been reported as one of the important factors that influence the growth of the organism and also the enzyme production in SSF (Baysal et al 2003;Shaktimay et al 2010). Sun et al (2009) further reported that moisture content was a factor that caused the swelling of the substrates thus gives effects on the gas exchange in the fermentation system.…”
Section: Resultsmentioning
confidence: 99%
“…The initial moisture content was set based on the moisture holding capacity of the substrate, the sago hampas. Moisture holding capacity of sago hampas was measured using method as described by Trautmann andKrasny (1997) and Shaktimay et al (2010). The amount of water retained was recorded and considered as 100% moisture holding capacity.…”
Section: Solid State Fermentation (Ssf)mentioning
confidence: 99%
See 1 more Smart Citation